A tecnologia de filmes de partículas de cálcio aplicada ao cafeeiro conilon : aspectos fisiológicos e agronômicos - Silva, Paulo Silas Oliveira da (2019)
This research was done in the coastal flatlands - region of Sergipe, Brazil with the general objective of elaborating calcium particle films for the conilon coffee plants (Coffea canephora Pierre ex A. Froehner), to evaluate its effects compared to natural shading in the crop establishment phase, and associated with different water regimes imposed on plants in the graining phase. For this purpose, two studies were done in different years, in 2017 and 2019 with the conilon coffee, variety "Vitória Incaper 8142". The first was done at the field in a randomized block design and factorial scheme 8x3 (n=4). The aim of this study was to evaluate ecophysiological parameters in response to the effects of four shading methods during conilon coffee establishment: natural shading by intercropping with banana trees, artificial shading with particle films (PF) of CaCO3 (10% w/v), and CaO (20% w/v) and plants in full sun (FS) (control), combined at two evaluation daily times (9:00h and 12:00h). The second factor was composed of three intervals of days after application (DAA) of the films (7DAA, 21DAA, and 35DAA). The second field study was laid out in subdivided plots (3x2), distributed in randomized blocks (n=4). Three water regimes made up the plots: 33%, 66% and 99% (control) of crop evapotranspiration (ETc); and two levels of artificial shading in the subplots: PF CaO (20% w/v) and FS, applied during the phenological stage of fruit graining. In both studies, it was found that natural shading and FP increased the net photosynthesis rate (A) while regulating excess stomatal conductance (gs) and transpiration (E) by reducing leaf and canopy temperature compared to FS control. These mechanisms favored the increase of instantaneous (WUE) and intrinsic (IWUE) use of water, while also favoring intercellular CO2 (Ci) and the carboxylation efficiency (ICE). Shaded plants showed reduced photoinhibitory processes expressed by lower non-photochemical energy dissipation values (Fo/Fm), while increasing the maximum photochemical efficiency (Fv/Fm), requiring time (21DAA) for acclimation and better results. It was also evidenced reductions in free proline osmoregulation and increase in relative water content (RWC%) in plants under 33% of ETc treated with particle films, compared to FS. During the establishment of the plants, the films provided protection and greater stability to daytime weather fluctuations. Already during the reproductive cycle also improved the water status and coffee graining, while reducing the effects of water deficit in coffee during the summer in the conditions of northeastern Brazil. These results verified in different years and periods showed that calcium particle films are valuable tools for coffee protection and have an innovative potential for different crop systems, 20% of CaO presented longer duration of these effects. It was also found that 'Vitória Incaper 8142' plants could support 66% ETc regimes, promoting water saving, and when associated with PF could improve plant performance and coffee grain size.